Response of rigid pavement resting on two-parameter soil medium subjected to moving load - Patil, V. A.; Sawant, V. A.; Deb, Kousik (Journal of Structural Engineering, 2024)
In recent years the study of the dynamic response of pavements to moving vehicle and aircraft loads has received significant attention because of its relevance to the design of pavements and airport runways. Finite Element Method is one of the best suitable mathematical tools used to analyse rigid pavements under moving vehicular or aircraft loads. Paper presents an improved solution algorithm based on Finite Element Method to analyse rigid pavements under moving vehicular or aircraft loads. The concrete pavement is discretized by beam elements. The underlying soil medium is modelled by Pasternak model which assumes the existence of shear interaction between the spring elements. This can be accomplished by connecting the spring elements to a layer of incompressible vertical elements which deform in transverse shear only. The deformations and forces maintaining equilibrium in the shear layer are considered by assuming shear layer as isotropic material. The equations of dynamic equilibrium are transformed from time variable t to a pseudo-time variable x (position of the vehicle), and then solved using Newmark-Beta integration scheme. A parametric study is conducted to investigate the effect of velocity of moving load, on the response of pavement. Results indicated that velocity of moving load had a significant effect on the response of the pavement.